REFLEKSI RASA SIMPATI DALAM NOVEL NARASI 2021 KARYA TENDERLOVA - Gani, Abdul; Maulinda, Aisyah Nurul; Fasah, Lukmanul Hakim; Mas’odi, Mas’odi; Nisa’, Tarisatun (Universitas Sultan Ageng Tirtayasa, 2025)
This research aims to identify a reflection of sympathy contained in the object, namely the novel Narasi 2021, using qualitative descriptive methods and a structuralism approach. The source of this research is a fiction book, namely an inspirational novel by Tenderlova which is a bilogy of her first novel, namely